Off The Job Training on Efforts to Improve Sdidtk Skills among Health Workers for Detecting Child Developmental Disorders - Teresia Elfi; Antonius Adolf Gebang; Yosefina Dhale Pora (GLOBAL HEALTH SCIENCE GROUP, 2024)
Stimulation, Detection, and Early Intervention for Child Development (SDIDTK) is one of the activities for monitoring the growth and development of toddlers aged 0-72 months to detect any developmental deviations in children of this age group. If deviations are found, early intervention is conducted as a corrective measure to restore normal growth and development or prevent further worsening of the deviation. The purpose of this study is to explain the impact of providing Off the Job Training (OJT) on SDIDTK for toddlers on increasing the knowledge of healthcare workers in the Nelle Health Center work area.This research is quantitative in nature. The study design is a quasi-experimental approach with a One-group Pretest-posttest Design. The instrument used was a questionnaire. Sampling was done using purposive sampling technique with a sample size of 30 respondents. The results of the study showed that before the OJT was given, the level of knowledge among healthcare workers was at a moderate level (56.7%) and low (43.3%). After the OJT was provided, there was an improvement, with good knowledge (70%) and moderate knowledge (30%). Based on the study's results, it can be concluded that there is an impact of off the job training on SDIDTK for toddlers on increasing the knowledge of healthcare workers in the Nelle Health Center work area. It is recommended that healthcare workers who have not yet participated in the training should seek opportunities to do so through various sources, while those who have already participated in SDIDTK training should implement it in accordance with the knowledge they have acquired.